Revalidation: Are we Meeting Training Needs? Training and its Influence on the Practice of Child Psychiatry and Psychotherapy - Kishore, Arun N. R. (Medknow Publications, 2010)
Revalidation and renewal of registration are issues of concern to most psychiatrists. Keeping up-to-date with current knowledge is an essential part of the renewal of license to practice. Training needs of psychiatrists are addressed in postgraduate courses and the gaps in training and updating of knowledge addressed through continuing medical education programs. This study aims to look at whether the training needs of psychiatrists working in the state of Kerala are being met. Two aspects of training and practice, child and adolescent psychiatry and psychotherapy, were assessed using a questionnaire. A significant number of respondents had not received any training in either of these areas in their postgraduate training. This did not affect their practice; most respondents continued to practice psychotherapy and see child patients despite not being trained. These two areas can thus be identified as lacunae in the curriculum as well as a need which should be addressed through Continuation Medical education programs.